Differences and similarities between IgG4-related disease with and without dacryoadenitis and sialoadenitis: clinical manifestations and treatment efficacy - Wang, Mu; Zhang, Panpan; Lin, Wei; Fei, Yunyun; Chen, Hua; Li, Jing; Zhang, Li; Zheng, Wenjie; Li, Yongze; Zeng, Xiaofeng; Zhou, Jiaxin; Lai, Yamin; et al. (Arthritis research & therapy, 2019)
This study aimed to compare the differences and similarities in the clinical manifestations and treatment efficacy of IgG4-related disease (IgG4-RD) in patients with and without dacryoadenitis and sialoadenitis (DS). A total of 121 untreated IgG4-RD patients in Peking Union Medical College Hospital were enrolled in this study. The patients were divided into three groups: DS-predominant (group A), non-DS (group B), and DS with other internal organs affected (group C). The patients were followed up for at least 15 months. Baseline and follow-up data were collected. The disease activity was evaluated according to the IgG4-RD responder index. The mean ± SD age at disease onset was 53.2 ± 14.1 years, and 71.9% of the patients were male. The prevalence of allergies was higher in groups A (21, 61.8%) and C (32, 69.6%) than group B (14, 34.1%). More patients with DS (17, 50.0%, and 17, 37.0%) had sinonasal lesions than those without DS (5, 12.2%). Moreover, an increased number of eosinophils were more common in patients with DS than in those without, as were increased serum IgG, IgG4, and IgE levels. More patients in group B and group C (28, 68.3%, and 31, 67.4%) received a combination therapy of corticosteroid and immunosuppressant. During the 15-month follow-up, 28 (23.1%) patients had disease relapse. Results demonstrated that IgG4-RD patients with DS had distinctive clinical features compared with non-DS. Allergy and sinonasal involvement were more common in patients with DS. Patients with DS showed higher serum IgG4 levels than those without DS.